PENGARUH PENAMBANGAN MANGAN TERHADAP KUALITAS AIR SUMUR DI DESA SUPUL, KECAMATAN KUATNANA, KABUPATEN TIMOR TENGAH SELATAN - Dorince Afgaretha Liu; Yofris Puay (Partner, 2020)
The aim of this study is to determine the effect of Manganese (Mn) mine in Supul village on the water quality of the residents' dug wells. Research method is used purposive sampling. Water sampling is required for chemical and biological analysis in the laboratory to determine the content of Fe, Mn, E. coli bacteria and pH level in the water. The results showed that the terms of threshold levels of Fe, Mn, and pH values, well water in Hamlet C (Oefenu) which is 200 to 300 meters away that is more polluted than others because those parameters are over the average threshold that required by the Ministry of Health on drinking and cleaning water quality standards. This condition is caused by very close to the mine site and the tailing Manganese.Keywords: Manganese mine, Well water quality, Supul Village